The Relationship of Audit Quality and Leverage on Tax Avoidance - Saputra, Alan Darma; Siburian, Matondang Elsa; Simorangkir, Enda Noviyanti; Tarigan, Aremi Evanta br. (Buhalterinės apskaitos teorija ir praktika, 2025)
This study explores the relationship between audit quality, financial leverage, and tax avoidance strategies in publicly traded non-financial firms in Indonesia from 2018 to 2022. Given that taxation is a key source of state revenue, variations in tax regulations and corporate incentives contribute to diverse tax avoidance practices. The research examines three dimensions of audit quality—audit tenure, audit specialization, and audit firm type—and their respective impacts on tax avoidance. Employing a quantitative approach with secondary financial data from 843 IDX-listed firms, the study applies the Feasible Generalized Least Squares (FGLS) method to mitigate heteroscedasticity and autocorrelation in panel data, enhancing the robustness of findings. Results reveal that audit specialization significantly reduces tax avoidance, suggesting that industry expertise among auditors strengthens compliance. However, audit tenure, audit firm type, and leverage exhibit no significant influence. These insights emphasize the need for greater awareness among auditors and policymakers regarding tax avoidance determinants within Indonesia's regulatory landscape. Future research should further explore external factors, such as the COVID-19 pandemic, and additional variables to provide a more comprehensive understanding of corporate tax behavior.
Keywords: tax avoidance; audit tenure; audit specialization; audit firm; leverage